More than kin: subordinates foster strong bonds with relatives and potential mates in a social bird. (17th September 2018) - Teunissen, Niki; Kingma, Sjouke A; Hall, Michelle L; Hidalgo Aranzamendi, Nataly; Komdeur, Jan; Peters, Anne
Abstract : In social species, individuals form relationships through repeated social interactions such as affiliation and aggression. By studying these interactions, we show that purple-crowned fairy-wrens form strong social bonds specifically with group members that are associated with benefits, while they use submissive behavior to reduce aggression from group members. Our findings help us understand how individuals benefit from being part of a group, and how social groups of individuals with divergent interests can remain stable. Abstract: Social interactions shape relationships between individuals in complex societies. Affiliative interactions are associated with benefits and strengthen social bonds, while aggressive interactions are costly and negatively affect social bonds. Individuals may attempt to reduce aggressive encounters through submissive displays directed at higher-ranking individuals. Thus, fine-scale patterns of affiliative, aggressive, and submissive interactions may reflect costly and beneficial social relationships within groups, providing insight into the benefits of group living and the mechanisms of conflict resolution. So far, however, most studies have looked at social interactions and benefits of group living in isolation. We investigated how the strength of social bonds (affiliative vs. aggressive interactions) and submissive displays varied with kin-selected and potential mating benefits, and with reproductive conflict in the cooperatively breeding purple-crowned fairy-wren, Malurus coronatus . Our results revealed that subordinates formed equally strong social bonds with kin and potential mates (unrelated opposite-sex individuals) while they formed antagonistic relationships with reproductive competitors that offered no kin-selected or mating benefits (unrelated same-sex individuals). Submissive displays were directed exclusively at same-sex breeders, regardless of relatedness. Affiliation and submission were associated with reduced foraging time when food was limited, indicating a cost to maintaining positive relationships. Together, our results suggest that the strength of social bonds is determined by (potential) benefits obtained from group members, while submission likely serves to reduce conflict. Our findings highlight the importance of time-costly social interactions for maintaining relationships with group members, providing insight into how social groups of individuals with (partly) divergent interests can remain stable.